2010
DOI: 10.4049/jimmunol.0903781
|View full text |Cite
|
Sign up to set email alerts
|

Different Proliferative Potential and Migratory Characteristics of Human CD4+ Regulatory T Cells That Express either CD45RA or CD45RO

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
170
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(196 citation statements)
references
References 50 publications
(87 reference statements)
20
170
1
5
Order By: Relevance
“…Accordingly, a recent study reported the lack of CD73 expression by circulating human CD4 1 Treg cells [38]. Furthermore, our results allocate the acquisition of CD73 to CD8SP cells in the thymus, which, on egress, will most likely enrich the pool of CD73 1 naïve CD8 1 T cells described in humans [39].…”
supporting
confidence: 53%
See 3 more Smart Citations
“…Accordingly, a recent study reported the lack of CD73 expression by circulating human CD4 1 Treg cells [38]. Furthermore, our results allocate the acquisition of CD73 to CD8SP cells in the thymus, which, on egress, will most likely enrich the pool of CD73 1 naïve CD8 1 T cells described in humans [39].…”
supporting
confidence: 53%
“…In agreement, the expression of CD45RA in CD4SP human thymocytes [37] and in FOXP3 1 CD4 1 T cells [28] was associated with low levels of CD25. In addition, the fraction of FOXP3 1 CD45RA 1 CD4 1 T cells expressing CD39 in the periphery was shown to be negligible [38].Conversely, we showed that the expression of CD73, an ectoenzyme that, in conjunction with CD39, generates the suppressive molecule adenosine, was mainly restricted to CD8SP cells, and this was observed irrespectively of FOXP3 expression. Accordingly, a recent study reported the lack of CD73 expression by circulating human CD4 1 Treg cells [38].…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Survival analysis and correlation of pretreatment percentages of the two Treg subsets with overall survival rate, showed that patients with higher percentages of nTregs had a better survival. nTregs differentiate into aTregs upon T-cell receptor stimulation by antigen recognition, 24,44,45 which could imply that patients having a relatively high percentage of peripheral nTregs have less tumor-specific Tregs. Due to their naïve phenotype, these nTregs are inefficient in infiltrating the tumor, 46 as is also illustrated by their low CCR4 expression, and thus these cells cannot exert immunosuppressive activity.…”
Section: Discussionmentioning
confidence: 99%